Neuropsychodynamic of anxiety - Salvatore Di Costanzo (International Journal of Psychoanalysis and Education, 2020)
Anxiety theory is very important in Freudian psychoanalysis, particulary the concept of signal anxiety which is central to unconscious conflict. According to the relational paradigm, anxiety is an interpersonal and affect regulation problem. Through affective neuroscience, Sullivan's interpersonal theory and Fonagy's mentalization theory, it is possible to develop a relational theory of anxiety. The amygdala plays an important role in implicit learning of relational representations characterized by anxiety, which inhibit affective regulation. Finally, some limits relating to the integration of psychoanalysis and neuroscientific research are presented.